ADAPTATION OF ARABIC SIGN LANGUAGE IN TEACHING FARDU AIN TO THE DEAF - Rashid , Syar Meeze Mohd (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The purpose of this study is to examine expert consensus on the adaptation of sign language in teaching Fardhu Ain to the Deaf. The study employed the Fuzzy Delphi Technique to gather agreement from experts proficient in sign language in response to the research questions. The instrument distributed contained 14 items designed to obtain expert consensus. The findings indicate that five key items should be adopted in Arabic Sign Language, namely signs related to the declaration of Shahadah, fundamental beliefs and tenets of Islam, personal cleanliness, aurat (modesty), and prayer. These items achieved a defuzzification value of 0.767, confirming their importance in supporting accessible religious education for the Deaf community.